Pre-salt: Geological formation, history of discoveries and evolution of production of oil and natural gas fields - Soares , Emilaine Maria de Souza Rangel; Ferreira, Geraldo de Souza (Seven Editora, 2023)
In 2006, Petrobras declared the discovery of reservoirs with significant amounts of high-grade API oil and gas located in a region below the salt layer, called the pre-salt, which extends along the southeast coast, from the state of Espírito Santo to the state of Santa Catarina. As it is a region that has not yet been explored, many doubts prevailed about what this layer would be, how the behavior of the salt works, how this system was formed and how it is possible for the oil to be trapped and be of such good quality in such an extreme and little-known environment, among other questions. This paper aims to present the geological formation of the pre-salt, the history of discoveries and the evolution of hydrocarbon production in the region in a time interval of 15 years. DOI:https://doi.org/10.56238/interdiinovationscrese-003